Evaluasi Ruang Terbuka Hijau di Kota Pekanbaru - Lis Noer Aini; Bambang Heri Isnawan; Endri Ridwan Saleh (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
The research was conducted to evaluate the availability of open green area in Pekanbaru  and to make the landscape model of green open area. This evaluation was needed to improve the functional and aesthetic value of green open area in Pakanbaru. The green areas were the main street of ring road, city park and forest. The research was carried out by using implementation methods of technical survey by observation, collective secondary and primary data. Election area was elected by purposive way and respondent method election done non-probability sampling technique that taking sample research by non-random way by 72 numbers of respondent. Data was analyzed by descriptive and spacial method, so continued by structuring of green open space to improve of develop functional value and aesthetic value in Pekanbaru. The research showed that the Pekanbaru City has 4,35% of green space in the shape of protecting areas, lake tours, and the grave till Pekanbaru City does not have wide green open space public as mandated by law no 26 year 2007 at least 20% from the areas spatial planning Pekanbaru, namely 49% of the area of Pekanbaru City. Planning model green lane road on Jl. Sukarno Hatta, Jl. Subrantas, Jl. Riau, Jl. Hang Tuah, Jl. Imam Munandar and Jl. Tuanku Tambusai based on the needs of the road to plant shade, windbreak and absorbing pollution. Planning Model urban forest planning was urban forest recreation by combining soft elements and hard elements. Planning model park junction Jl. Subrantas based on plant shade needs and space for the interaction for market users.